2016
DOI: 10.1002/rcr2.174
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical course of idiopathic pulmonary haemosiderosis with rheumatoid arthritis

Abstract: Idiopathic pulmonary haemosiderosis (IPH) is a rare cause of diffuse alveolar haemorrhage during childhood, and its precise pathophysiology and long‐term clinical course remain unclear. A 31‐year‐old man was diagnosed with IPH at four years of age and had recurrent episodes of haemoptysis. The patient's symptoms responded well to steroids. However, pulmonary fibrosis and the cystic region in the lung progressively worsened. At age 27, the patient developed polyarthritis with positive anti‐cyclic citrullinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In addition, some studies have shown that if ImPH is treated effectively in the early stages, the severity of JIA can be reduced, and even the occurrence of JIA can be avoided. This fully affirms the importance of early diagnosis and timely treatment of ImPH 20‐22 …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, some studies have shown that if ImPH is treated effectively in the early stages, the severity of JIA can be reduced, and even the occurrence of JIA can be avoided. This fully affirms the importance of early diagnosis and timely treatment of ImPH 20‐22 …”
Section: Discussionsupporting
confidence: 78%
“…This fully affirms the importance of early diagnosis and timely treatment of ImPH. [20][21][22] To our knowledge, this is the first report of case series about JIA presenting as DAH at onset. Considering the limitations of the small numbers of cases in our study, there may have been some selection bias.…”
Section: Managements and Outcomesmentioning
confidence: 99%